CASHFLOW PLANNING ON THE BULUKUMBA STATE COURT BUILDING PROJECT PHASE II - Wudi Darul Putra; Hanafi Ashad (Moeslim Indonesian University (UMI), 2018)
Cashflow planning is inseparable from scheduling conditions which include EST (earliest start time) or the earliest project start time, LST (latest start time) or the slowest project start time, and the use of non-critical activity floats which are a combination of the two, where activities in the project is collected in the middle. Thus, it is necessary to conduct a study to further examine cash flow planning in a construction project to obtain an optimal cash flow concept, which in the end can obtain maximum profit. This study aims to [1] Optimal cash flow planning in order to obtain maximum profit, from the payment model without a down payment, scheduling conditions for EST, LST and Optimum Shift. [2] Optimal cash flow planning in order to obtain maximum profit, with 20% down payment and 30% down payment, scheduling conditions for EST, LST and Optimum Shift. [3] Get a Project Scheduling scenario that can generate optimal cash flow, in other words the cash flow that generates the greatest profit. The results showed that [1] Conditions Without Down Payment with Monthly Payments, resulted in 9.29% Profit, the largest Overdraft was Rp. 1,533,680,766.00 CV =+, SV=+. [2] Conditions with 20% down payment and payment terms according to progress, resulting in 9.29% Profit, the biggest Overdraft Rp 848,581,656.00 CV =+, SV=+. [3] For conditions with 30% down payment and payment according to the progress terms, it generates 9.29% Profit, the largest Overdraft is IDR 586,319,072.00CV =+ , SV=+. And [4] Downpayment can indirectly affect profits, if when an overdraft occurs, the contractor cannot have sufficient funds so that they have to borrow funds from a third party, resulting in fluctuating interest expenses.